The lived experiences of residents living near the sanitary landfill in Barangay Calajunan, Mandurriao,Iloilo City amidst the Covid-19 pandemic Aohd Austin R. Alegoro and Marc Leo H.Layson. - Alegoro, Aohd Austin Joash R.
The COVID-19 pandemic had a significant impact on the Philippines' waste management system, including open dumpsites and landfills where COVID-19 wastes are processed and disposed, which in turn affected the way of life the people who depend on these facilities for survival. This study aims to describe the lived experiences of residents living near the sanitary landfill in Barangay Calajunan, Mandurriao, Iloilo City amidst the COVID-19 pandemic and to draw out lessons from these lived experiences that can improve current and future waste management practices and to advance the welfare of people living near the sanitary landfill. Particularly, this study focuses on the residents' life as individuals, as members of the community, residents' life in relation to their work, and the Iloilo City waste management amidst the pandemic. The data were collected through Key Informant Interviews and in-depth semi-structured interviews and were then analyzed using Collaizi's Descriptive 7 Step Phenomenological Method. The study revealed that the pandemic altered the way the residents lived their lives around the landfill. These changes were caused by the policies and regulations implemented by the LGUs of Iloilo City and Barangay Calajunan as well as the changes that the landfill had undergone to adapt to the COVID-19 pandemic, this affected the residents who live near the landfill as their lives are intertwined with the waste management process of the landfill as Waste Pickers. Although there were many themes that were shared by the men and women residents in terms of their individual, communal, and work lives, there were other themes exclusive to only a particular sex that emerged. Further study is required in these specific areas because some of the themes found in this study contradict the reviewed literature or are unrecorded phenomena without any existing material to support or refute the findings. Keywords: sanitary landfill, waste management, lived experiences, COVID-19, pandemic